2023
DOI: 10.3390/nu15041031
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Effects of Natural Products on Inflammatory Bowel Disease In Vivo and Their Mechanisms: Based on Animal Experiments

Abstract: Inflammatory bowel disease (IBD) is a chronic, non-specific inflammatory disease of the intestine that can be classified as ulcerative colitis (UC) and Crohn’s disease (CD). Currently, the incidence of IBD is still increasing in developing countries. However, current treatments for IBD have limitations and do not fully meet the needs of patients. There is a growing demand for new, safe, and highly effective alternative drugs for IBD patients. Natural products (NPs) are used in drug development and disease trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0
10

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 335 publications
0
15
0
10
Order By: Relevance
“…Several reviews have been written on NPs as sources of new drugs [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ], yet no in-depth discussions of biodiscovery approaches and NP isolation and characterisation techniques have been reported previously. Hence, the current review aims to discuss the approaches used in selecting the starting materials, various extraction methods and modern techniques currently available for identifying anti-inflammatory small molecules from NP.…”
Section: Introductionmentioning
confidence: 99%
“…Several reviews have been written on NPs as sources of new drugs [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ], yet no in-depth discussions of biodiscovery approaches and NP isolation and characterisation techniques have been reported previously. Hence, the current review aims to discuss the approaches used in selecting the starting materials, various extraction methods and modern techniques currently available for identifying anti-inflammatory small molecules from NP.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the management of UC primarily depends on the administration of medications including anti-inflammatory agents, immunosuppressants, biologics, and antibiotics [5] . Although these medications can alleviate the symptoms of UC, they also have significant drawbacks, such as prolonged treatment duration, adverse side effects [6] , increased drug dependency [7] , and the occurrence of complications in the liver, gallbladder, and eyes [8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that certain natural dietary supplements demonstrated promising therapeutic effects in the occurrence and development of UC. Examples include natural polysaccharides, proteins, polyphenols, and flavonoid compounds, among others [5,[10][11] . This suggests that naturally sourced functional ingredients may have been candidate drugs for treating UC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…have been discovered from natural sources for their antimicrobial, cardioprotective, anti-inflammatory, anticancer and chemoprotective activities. There is considerable evidence to suggest that these phytochemicals are beneficial to health on an epidemiological and clinical level ( Chan et al, 2023 ; Du et al, 2023 ; Rahaman et al, 2023 ; Xu et al, 2023 ; Zhou et al, 2023 ; Zhu et al, 2023 ).…”
mentioning
confidence: 99%